Cardiac Involvement in Glycogen Storage Disease Type IV: Two Cases and the Two Ends of a Spectrum. (26th September 2012) - Aksu, Tolga; Colak, Ayse; Tufekcioglu, Omac
Abstract : Glycogen storage disease type IV (GSD IV) is an autosomal recessive disorder due to the deficiency of α 1, 4-glucan branching enzyme, resulting in an accumulation of amylopectin-like polysaccharide in various systems. We describe two cases, a 23-year-old girl with dilated cardiomyopathy who presented with progressive dyspnea and fatigue and a 28-year-old girl with hypertrophic cardiomyopathy who was asymptomatic, secondary to the accumulation of amylopectin-like fibrillar glycogen, in heart. In both patients, the diagnosis was confirmed by enzyme assessment. Our patients showed that GSD IV is not only liver or skeletal muscle disease, but also it can be presented in different form of the spectrum of cardiomyopathy from dilated to hypertrophic and from asymptomatic to decompensated heart failure. Also, to our knowledge, this is the first hypertrophic cardiomyopathy case due to GSD IV in the literature.